Determining selection criteria in finger millet (Eleusine coracana) genotypes using multivariate analysis - SHARMA, NIDHI; BANDYOPADHYAY, B B; CHAND, SUBHASH; PANDEY, P K; BASKHETI, D C; MALIK, ANKIT; CHAUDHARY, RAJAT (The Indian Journal of Agricultural Sciences, 2022)
Finger millet [Eleusine coracana (L.) Gaertn.] grows in upland rainfed conditions customarily at disadvantageousregions of the country. Evaluation of genetic diversity and the choice of parents is the crucial step to augmenting the desired improvement of crops towards grain and fodder yield. In the present study, 31 finger millet genotypes were studied for genetic diversity employing cluster and principal component analysis (PCA) at G. B. Pant Universityof Agriculture and Technology (GBPUA&T), Pantnagar during 2018 and 2019. Mahalanobis D2 statistics revealedseven clusters where cluster I represented 24 genotypes, cluster II with two genotypes, and the remaining clusterswith a single genotype each. The maximum inter-cluster distance was observed between clusters III and VII (49.783)followed by III and IV (46.737) indicating more diversity between clusters. Five PCs accounted for 77.50% of totalgenetic variability using PCA. Furthermore, two diverse and complementary parents (PKPS4 and F20) were identifiedthat possessed complement traits, viz. bold seed, high mean for single head weight, grain yield, harvest index, number of finger/spike (PKPS4), and number of tillers/plant (F20). Therefore, PKPS4 and F20 genotypes could be considered as donor parents for different traits to increase grain yield in finger millet.